2018
DOI: 10.1186/s13072-018-0227-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel antisense noncoding RNA, ALID, transcribed from the putative imprinting control region of marsupial IGF2R

Abstract: BackgroundGenomic imprinting leads to maternal expression of IGF2R in both mouse and opossum. In mouse, the antisense long noncoding (lnc) RNA Airn, which is paternally expressed from the differentially methylated region (DMR) in the second intron of Igf2r, is required to silence the paternal Igf2r. In opossum, however, intriguingly, the DMR was reported to be in a different downstream intron (intron 11) and there was no antisense lncRNA detected in previous analyses. Therefore, clarifying the imprinting mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Most recently, continuing our collaboration with Shunsuke Suzuki we showed that there is a lncRNA (ALID) in the marsupial IFG2R locus. This gene is the best candidate factor for establishing the paternal silencing of marsupial IGF2R but without the transcriptional overlap that occurs in the mouse Ifg2r locus with its lncRNA Airn (Suzuki et al 2018). The tammar also shares the same process of global methylation of germ cells as other mammals, although as expected, the timing differs, being postnatal in the tammar and pre-natal in eutherians (Ishihara et al 2019).…”
Section: Father's Influence On the Offspring: Genomic Imprintingmentioning
confidence: 88%
“…Most recently, continuing our collaboration with Shunsuke Suzuki we showed that there is a lncRNA (ALID) in the marsupial IFG2R locus. This gene is the best candidate factor for establishing the paternal silencing of marsupial IGF2R but without the transcriptional overlap that occurs in the mouse Ifg2r locus with its lncRNA Airn (Suzuki et al 2018). The tammar also shares the same process of global methylation of germ cells as other mammals, although as expected, the timing differs, being postnatal in the tammar and pre-natal in eutherians (Ishihara et al 2019).…”
Section: Father's Influence On the Offspring: Genomic Imprintingmentioning
confidence: 88%
“…As research has progressed, ncRNAs such as microRNAs (miRNAs), long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) have been found to participate in cellular signalling and regulation of various processes [9][10][11]. In recent years, as transcripts have been shown to exceed 200 bp, lncRNAs have been proven to control gene regulation, organ differentiation and both developmental and pathological processes [12][13][14]. Moreover, studies have indicated that lncRNAs participate in pancreatic and islet development, β-cell formation and function and T cell differentiation in vitro [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, opossum pups are born on embryonic day 14, at the same stage of a 6-week human embryo or E11.5 mouse embryo, which enables many kinds of early embryonic studies that cannot be easily conducted with eutherians, in which access to embryos and fetuses at these stages requires considerable disruption of the gestational environment (Cardoso-Moreira et al 2019; Mahadevaiah et al 2020). Marsupials are also valuable for investigating major epigenetic processes such as X-chromosome inactivation (Hornecker et al 2007; Grant et al 2012; Rodriguez-Delgado et al 2014; Wang et al 2014; Waters et al 2018; Mahadevaiah et al 2020) and genomic imprinting (Weidman et al 2006; Lawton et al 2008; Das et al 2012; Douglas et al 2014; Suzuki et al 2018). M. domestica has been used in many medical and disease studies, such as gene expression during neural development (Dooley et al 2012; Sears et al 2012; Pavan et al 2014; Wheaton et al 2021), hypercholesterolemia and steatohepatitis (Chan et al 2010; Chan and VandeBerg 2011; Chan et al 2012), cancer therapy and prevention (Nair and VandeBerg 2012; Nair et al 2014), immunogenomics (Parra et al 2008; Morrissey et al 2021; Schraven et al 2021), viral pathogenesis (Thomas et al 2019), and influence of biological sex on social behavior, individual recognition, and associative learning (Gil et al 2019).…”
Section: Introductionmentioning
confidence: 99%